2012
DOI: 10.1111/j.1467-8535.2012.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions, beliefs and concerns about cyberbullying

Abstract: Schools and teachers nowadays face new difficulties and challenges as a result of the fast growth of cyberbullying. The aim of the study is to examine the perceptions, beliefs and concerns about cyberbullying, as well as the needs, of a professionally diverse group of teachers. Three‐hundred and twenty‐eight teachers (88.4% female, 11.6% male) from different types of schools and professional foci were randomly selected and completed a cyberbullying questionnaire regarding their perceptions of cyberbullying and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
23

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 27 publications
6
73
0
23
Order By: Relevance
“…Recently, in a study of 266 Portugese teachers, Moreira, Pinheiro, Gomes, Cotter and Ferreira (2013) found that male teachers reported significantly greater difficulties than female teachers in promoting students' socialemotional skills. Meanwhile, in the relatively new research field about the impact of cyberbullying on students' wellbeing, Eden, Heiman and Olenik-Shemesh, (2013) reported a study that administered a questionnaire about cyberbullying to 328 Israeli teachers from diverse school settings. Eden et al found that female teachers were more concerned about cyberbullying, expressed a higher belief in the school's commitment to deal with cyberbullying and had more belief in the importance of learning about cyberbullying.…”
Section: Teachers Are At the Core Of Promoting Mental Health In Schoolsmentioning
confidence: 99%
“…Recently, in a study of 266 Portugese teachers, Moreira, Pinheiro, Gomes, Cotter and Ferreira (2013) found that male teachers reported significantly greater difficulties than female teachers in promoting students' socialemotional skills. Meanwhile, in the relatively new research field about the impact of cyberbullying on students' wellbeing, Eden, Heiman and Olenik-Shemesh, (2013) reported a study that administered a questionnaire about cyberbullying to 328 Israeli teachers from diverse school settings. Eden et al found that female teachers were more concerned about cyberbullying, expressed a higher belief in the school's commitment to deal with cyberbullying and had more belief in the importance of learning about cyberbullying.…”
Section: Teachers Are At the Core Of Promoting Mental Health In Schoolsmentioning
confidence: 99%
“…Eden, Heiman, Olenik-Shemesh [7] survey highlighted the need to encourage the teachers to design and to plan appropriate actions to prevent cyberbullying. Moreover, teachers, who participated in the survey, suggested that urgent attention must be paid to three aspects: policy making, enhancing awareness of a school team and coping strategies for parents.…”
Section: The Prevalence Of Cyberbullying and The Views Of 5-12 Grade mentioning
confidence: 99%
“…A need existed for the qualitative research case study that was conducted at one middle school in Western United States, because of the frequency of disruptions and fights in the classrooms associated with bullying and cyber bullying. The school predicament is supported in the literature by some researchers when they revealed that there has been an escalation in the number and frequency of incidents of bullying, particularly cyberbullying, in today's schools (Eden et al, 2013;Gofin & Avitzor, 2012;Hinduja & Patchin, 2011). This problem is exacerbated by the utilization of contemporary technologies, such as cell phones, computers, tablets, and social media, such as Facebook, Instagram, and Twitter (Dey Rey et al, 2012;Gofin & Avitzor, 2012;Hinduja & Patchin, 2011).…”
Section: Problem Statementmentioning
confidence: 76%
“…This is in sharp contrast to the typical single-session school assembly on bullying, which some of the participants alluded to, which increased bullying awareness but were not followed through. Research highlights the importance of providing a class time after a major assembly to discuss bullying and cyber bullying (Austin et al, 2012;Eden et al, 2013). Utilizing the lessons learned from such an assembly to foster emotional and social skills, effective communications and appropriate strategies for responding to bullying incidents is essential (Austin et al, 2013).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation